Competent and deficient provision of childbirth services: a descriptive observational study assessing the quality of intrapartum care in two provinces of the Democratic Republic of the Congo - Stephan Brenner; Supriya Madhavan; Céline Kanionga Nseya; Claude Sese; Günther Fink; Gil Shapira (BMC, 2022)
Abstract Background A majority of women in the Democratic Republic of the Congo (DRC) give birth in a health facility, but maternal and newborn mortality remains high. In rural areas, the quality of facility-based delivery care is often low. This study examines clinical quality of intrapartum care in two provinces of the DRC. Methods We observed process and input elements of delivery care provision at 29 facilities in Kwilu and Kwango provinces. Distinguishing non-performance attributable to provider behavior vs. input constraints, we compared both providers' adherence to clinical standards ("competent care") and non-adherence to processes for which required inputs were available ("deficient care"). Results Observing a total of 69 deliveries, care was most competent for partograph use (75% cases) and hemorrhage prevention (73%), but least for postpartum monitoring (4%). Competent care was significantly associated with higher case volumes (p = ·03), skilled birth attendance (p = ·05), and nulliparous women (p = ·02). Care was most deficient for infection prevention (62%) and timely care (49%) and associated with cases observed at hospitals and lower delivery volume. Conclusions Low quality was commonly not a result of missing equipment or supplies but related to providers' non-adherence to standard protocols. Low case volumes and the absence of skilled attendants seemed to be main factors for sub-standard quality care. Birth assistance during labor stage 2 was the only intrapartum stage heavily affected by the unavailability of essential equipment. Future interventions should strengthen links between birth attendants' practice to clinical protocols.